Association between non-high-density lipoprotein to high-density lipoprotein cholesterol ratio and bowel health in U.S. adults: a cross-sectional study - Liu, Wei; Liu, Qirui; Jiao, Cheng; Guo, Jun; Zhang, Lipu; Zhang, Yao; Liu, Guangchao (Frontiers in Physiology, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a robust predictor of dyslipidemia and cardiovascular disease, strongly linked to the development of various chronic conditions. However, there is a paucity of evidence exploring the relationship between NHHR and bowel health, particularly chronic diarrhea and constipation.MethodsThis cross-sectional study utilized data from the National Health and Nutrition Survey (NHANES) 2005–2010. Sociodemographic, lifestyle, and health status data were collected alongside blood lipid levels. Weighted multivariate logistic regression models assessed the association between NHHR and bowel health. The restricted cubic spline (RCS) method was used to explore their dose-response relationship. Subgroup analyses and sensitivity analyses were conducted to further validate the robustness of our findings.ResultsIn our study of 11,268 participants, a significant positive association was identified between elevated NHHR levels and chronic constipation in women, with the highest quartile showing an adjusted OR of 1.57 (95% CI: 1.21–2.03) compared to the lowest quartile. This association was notably stronger among female smokers. Sensitivity analyses excluding individuals with hypercholesterolemia or inflammatory bowel disease confirmed the robustness of the correlation. No significant associations were found in men.ConclusionThe study findings provide novel evidence of the relationship between NHHR and bowel health in United States women, particularly chronic constipation. However, the cross-sectional design of the study limits our ability to establish causality. Additionally, reliance on self-reported bowel health data may introduce inaccuracies. Further research is needed to explore the mechanisms underlying this association and the impact of lifestyle factors.